Aplikasi dan Sistem Pemantau Gizi Balita Melalui Berat dan Tinggi Badan Bayi untuk Pelayanan Posyandu Anyelir 1 Surabaya Berbasis Internet of Things - Mutiara Sari, Dewi; Izzudin Nadhori, Isbat; Hadiah Muliawati, Tri; Wahyuda, Imam; Fatrian Romadhoni, Achmad; Arissabarno, Cahyo; Adhitama Nugroho, Farrel; Jasmine Azzahra, Soniya; Andhika Ardianto, Arya; Azzahra, Salsabilla; Nur Fadhillah, Wiradika (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Based on Ikatan Dokter Anak Indonesia (IDAI), one of the indicators used to monitor the physical growth and development of healthy children is through body weight. It is recommended that in infancy, parents routinely monitor the baby's weight and height. In Indonesia, there is a posyandu program that facilitates regular checking of baby's weight. Currently the monitoring system for baby weight and height at Posyandu Anyelir 1 Surabaya is still done manually, namely weighing babies on traditional scales and manual height, then manually recording them on the Towards Healthy Card (KMS) both in the cadre records and parents of toddlers. This makes monitoring less well recorded, especially if the KMS is lost. So that the PENS Community Service program makes Smart Posyandu Products: Applications and Toddler Nutrition Monitoring Systems Through Baby Weight and Height for Posyandu Services Based on the Internet of Things. By applying the case study method to implementing Smart Posyandu Products at posyandu, Smart Posyandu Products can be accepted by the Posyandu. So that the results of community service activities can help the duties of posyandu cadres and parents of toddlers in monitoring toddler nutrition effectively and efficiently.